Improvement of Pain Symptoms in Musculoskeletal Diseases After Multimodal Spa Therapy in the Austrian Gastein Valley-A Study Based on Longitudinal Registry Data - Antje van der Zee-Neuen; Antje van der Zee-Neuen; Antje van der Zee-Neuen; Antje van der Zee-Neuen; Antje van der Zee-Neuen; Julia Fuchs; Julia Fuchs; Julia Fuchs; Julia Fuchs; Sonja Wildburger; Sonja Wildburger; Sonja Wildburger; et al. (Frontiers Media S.A., 2023)
Objective: The study aim was to investigate the course of pain in rest and motion in seven different rheumatic diseases (RMD), prior and after multimodal spa therapy including low-dose radon treatment and at 3-, 6-; and 9-month follow up.Methods: Complete data from the radon indication registry including information on 561 subjects with RMD were analysed to explore the association of timepoint of measurement with pain in rest and motion. For this purpose, linear regression models adjusted for RMD-type, age, sex and body mass index (BMI) were applied.Results: The mean age of the sample was 55 years, the average body mass index was 26.8, and 275 subjects were women. Pain scores were significantly improved at all-time points compared to baseline. Pain courses were different for each RMD with the largest improvement seen in fibromyalgia.Conclusion: Timing spa facility visits according to RMD-specific pain courses may result in sustained pain reduction.